THE CONCEPT OF TEACHER BURNOUT AND HOW STRIVING TO HELP LEARNERS ACQUIRE LANGUAGE, AND BEING A SUCCESSFUL TEACHER IN GENERAL - Guliniso Nigmatova (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2021)
This article examines the concept of teacher burnout and how the desire to help students master the language and be a successful teacher in general can sometimes exhaust teachers and force them to quit teaching. The author wanted to share a few ideas that will help teachers stay upbeat and avoid some of the pitfalls that can lead to teacher burnout. First of all, the author discusses the importance of network formation. The main purpose of the article is to help teachers avoid teacher burnout-to maintain a sense of self-control. Teachers can maintain this feeling by focusing on what they can do, rather than what is beyond their control. Maintaining a sense of self-control also comes from finding a work-life balance at home. The author concludes that the last way to avoid teacher burnout is to find a passion that teachers genuinely care about. This means that teachers are guided by fundamental principles and that they continue to improve on the basis of these principles.